Keramik Takalar 1981-2010: Ragam Bentuk dan Perubahan - Irfan Irfan; Dharsono Dharsono; SP. Gustami SP. Gustami; Guntur Guntur (PANGGUNG, 2019)
ABSTRACTThe pottery in Takalar regency, South Sulawesi province, has been existed for hundreds of years and has become part of a community cultural life. The study aims to identify the changes ofvarious ceramic forms and design from 1981 to 2010. This periodisation is chosen because in the 1980s the Department of Industry and Trade had supervised craftsmen in Takalar, which has given significant changes in the development of ceramics in the area. The method employed is a qualitative method with a multidisciplinary approach, including history and ethnography. To analysis the data, the research uses interactive techniques (Miles dan Hubermen, 1992). The research site covers three districts: Sandi, Pabbatangan, and Pakalli. The study shows there are significant changes in ceramic forms and design from 1980 to 2010. Based on the classification used, the changes are divided into three periods: traditional forms (1981-1990), transition forms (1991-2000), and modern forms (2001-2000). These changes are caused by the open attitude of the craftsman to outside agencies, such as Disperindag (government), universities, and consumers. These outside parties have influenced artisans to develop ceramic designs by introducing new shapes and values, including foreign cultures.Keywords: ceramic development, design and form changes, and craftsmentABSTRAKKeberadaan keramik di Kabupaten Takalar, Sulawesi Selatan, telah berlangsung selama ratusan tahun dan menjadi bagian kehidupan sosial budaya masyarakatnya. Penelitian ini bertujuan untuk mengidentifikasi ragam bentuk dan perubahan desain keramik sejak tahun 1981 hingga tahun 2010. Periodisasi ini dipilih sebab sejak tahun 1980-an Disperindag telah membina perajin keramik di Takalar yang telah memberi dampak perubahan. Metode yang digunakan adalah metode kualitatif dengan pendekatan multidisiplin, yakni sejarah dan etnografi. Lokasi penelitian terbagi ke dalam tiga kecamatan, dengan lokasi sentra di Sandi, Pabbatangan, dan Pakalli. Adapun analisis data menggunakan teknik interaktif (Miles dan Hubermen, 1992). Hasil penelitian menunjukkan telah terjadi perubahan bentuk sejak tahun 1981 hingga tahun 2010. Klasifikasi berdasarkan perubahan bentuk terbagi pada tiga periode, yakni tradisional (1981-1990), transisi (1991-2000), dan modern (2001-2010). Perubahan desain disebabkan para perajin bersikap terbuka terhadap pihak eksternal seperti Disperindag, perguruan tinggi, dan konsumen. Pihak eksternal memperkenalkan bentuk dan nilai baru, termasuk unsur budaya luar, membimbing, dan mempengaruhi para perajin agar mengembangkan desain keramik.Kata kunci: perkembangan keramik, perubahan bentuk dan desain, perajin